Academic life - Article Editorial (Ибероамериканские тетради)
October and November 2023 saw a lot of various academic events dedicated to Ibero-American research, in which prominent experts from various Russian educational and research centers, as well as representatives of several Latin American countries, Spain and Portugal took part. The academic forums served as a platform for the exchange of ideas on the evaluation of the development of relations with the countries of Latin America and the Caribbean and the opportunities to expand academic contacts, better understanding and cooperation with Russia in various areas.